Hand-arm vibration disorder among grass-cutter workers in Malaysia. Issue 3 (2nd July 2016) - Azmir, Nor Azali; Ghazali, Mohd Imran; Yahya, Musli Nizam; Ali, Mohamad Hanafi
Abstract : Introduction. Prolonged exposure to hand-transmitted vibration from grass-cutting machines has been associated with increasing occurrences of symptoms and signs of occupational diseases related to hand–arm vibration syndrome (HAVS). Methods. A cross-sectional study was carried out using an adopted HAVS questionnaire on hand–arm vibration exposure and symptoms distributed to 168 male workers from the grass and turf maintenance industry who use hand-held grass-cutting machines as part of their work. The prevalence ratio and symptom correlation to HAVS between high and low–moderate exposure risk groups were evaluated. Results. There were positive HAVS symptoms relationships between the low–moderate exposure group and the high exposure group among hand-held grass-cutting workers. The prevalence ratio was considered high because there were indicators that fingers turned white and felt numb, 3.63, 95% CI [1.41, 9.39] and 4.24, 95% CI [2.18, 8.27], respectively. Less than 14.3% of workers stated that they were aware of the occupational hand–arm vibration, and it seemed to be related to the finger blanching and numbness. Conclusion. The results suggest that HAVS is under-diagnosed in Malaysia, especially in the agricultural sectors. More information related to safety and health awareness programmes for HAVS exposure is required among hand-held grass-cutting workers.